DEVELOPMENT OF TEACHER PROFESSIONALISM THROUGH MANAGERIAL LEADERSHIP OF MADRASAH HEADS IN MAN 3 AND MAN 4 BANJAR - Nurhasanah, Nurhasanah (Universitas Lambung Mangkurat, 2025)
This study aims to describe the leadership of madrasah principals in developing teacher professionalism at MAN 3 and MAN 4 Banjar, the development models implemented, and the strategies used. The research employed a qualitative approach with a multi-site study design. Data were collected through interviews, observations, and documentation. The findings show that principals play a central role in planning, implementing, and evaluating teacher professional development programs. The development models include training, workshops, academic supervision, and coaching. The strategies involve empowering teachers, collaborating with external institutions, and utilizing resources optimally. This study indicates that the success of professional development programs is significantly influenced by visionary, participatory, and transformative managerial leadership of the principals.